Maxillary Sinus Cysts: Aetiology, Pathogenesis, Treatment Modalities, And Prophylaxis (Progress Annals: Journal of Progressive Research, 2026)
This article presents a comprehensive scientific analysis of the underlying causes (aetiology) and developmental mechanisms (pathogenesis) of maxillary sinus cysts, which represent one of the most widely encountered pathologies within the clinical practice of otorhinolaryngology. Furthermore, the paper elucidates the differential diagnostic characteristics of retention and odontogenic cysts, critically evaluating their consequent impact on the respiratory tract and adjacent anatomical structures, with a particular emphasis on middle ear functionality. In addition to these pathophysiological considerations, the study provides a detailed exposition of contemporary diagnostic modalities, minimally invasive treatment interventions such as functional endoscopic sinus surgery (FESS), and targeted prophylactic measures designed to prevent the onset and recurrence of the condition.